Implementation of customary law values in a traditional marriage of the Timorese in realizing laws based on local wisdom - Benediktus Peter Lay; Stefanus Don Rade; Maria Theresia Geme (Trigin Publisher, 2023)
Customary law is one of the legal systems recognized for its existence empirically in terms of the legal dogmatics approach and the legal, sociological approach. The customary law of marriage in the Timorese tribe is one of the ancestral cultural products of the people of the Timorese tribe that must be maintained and appropriately maintained to preserve the continuity of noble cultural values as local wisdom in building laws based on local knowledge. The Timorese marriage ceremony contains values and norms that must be understood by the Timorese people, looking at several aspects related to the conditions of the times that always move towards modern and advanced changes so that cultural values that can build laws based on local wisdom are not eroded. This research is a type of normative legal research using the sociology of legal history and legal anthropology approach to find and reveal the values of customary law as a product of community culture which contains local wisdom values. Based on research on traditional marriage in the Timorese tribe of Tetaf Village, there are four stages and eight values that harmonize with each other in the values contained in the customary marriage procedures of the Tetaf community, which should be an aspired legal construction, in building laws based on local wisdom to maintain, restore, and preserve local customs and culture which are the basis for achieving human welfare, with positive customary law values.